Migration, Diversity, and Economic Growth. A Replication Study of Bove and Elia (World Development, 2017) - Bianca Balsimelli Ghelli; Luigi Ventura (Journal of Comments and Replications in Economics (JCRE), 2024)
This study examines the antecedents of Mobile banking (M-banking) app adoption, explores post-adoption effects, and tests the moderating effect of consumer status orientation on the relationship between adoption intention and its consequences. The conceptual model hypothesized 20 relationships, including 10 moderations. Hypotheses are tested using the structural equation modeling method (PLS-SEM) on a sample of 509 individuals. The results reveal that the main variables of 'users' rational perception, namely behavioral control and terminal security, significantly influence the intention to adopt the application, which in turn impact relationship quality and financial inclusion. However, hedonic expectations do not have a significant impact on the intention to adopt the application; the impact of culture in these relationships is further established; indeed, traditional and modern values moderate the impact of the intention to adopt the application on key post-adoption factors, financial inclusion, and relationship quality. The main recommendations and limitations of the research are discussed.A recent and well known paper, Bove and Elia (2017), argues that migrants' diversity, as captured by the indexes of both fractionalization and polarization, exerts a positive effect on GDP growth. In fact, by using the same dataset and methodology, we show that the impact of diversity cannot be distinguished from that of migration itself due to the very high correlation among the corresponding variables. Also, if one disentangles migration from diversity, following Alesina et al. (2016), only migration maintains a positive impact on growth while diversity, as captured by fractionalization, turns out to be weakly and positively associated with growth, but limitedly to the 1980-2010 time span. Polarization, on the other hand, does not seem to exert any effect on growth. The question as to whether diversity is more or less beneficial in terms of economic growth remains therefore an intriguing one, and calls for more theoretical and empirical analyses, possibly based on less (geographically) aggregated data.
https://doi.org/10.15456/j1.2024093.1253206165
Keywords: C23; C51; E21; F36; 330; Diversity; Economic Growth; Migration; Replication